THE CAMBRIAN OF THE SEVERNAYA ZEMLYA ARCHIPELAGO, RUSSIA - Bogolepova O.K.; Gubanov A.P.; Raevskaya E.G. (My University, 2001)
The Lower Paleozoic strata belonging to the Kara Basin are extensively exposed in the Severnaya Zemlya Archipelago. During the Cambrian, thick clastic sequences are the dominating sediments on Severnaya Zemlya. The Cambrian rocks occur in the Nekrasovskaya, Maratovskaya, Universitetskaya and Kurchavinskaya formations. Short descriptions of the main lithological and faunal features of each formation are given. Based on new palaeontological data, the age of the Kurchavinskaya Formation is clarified. Successions straddling the Cambrian/Ordovician boundary show a break in the late Cambrian stratigraphy of Severnaya Zemlya, which was caused by the (?) early Ordovician unconformity. Based on faunal evidences, the best palaeolatitudional position of the Kara microplate is estimated between 30°-40° of the southern latitudes and in the vicinity of Baltica and Siberia.
Keywords: Cambrian; Paleozoic; Ordovician; Severnaya Zemlya Archipelago; Paleozoic; Paleozoic::Ordovician; Paleozoic::Cambrian; Палеозой; Палеозой::Ордовикская; Палеозой::Кембрийская